1968
DOI: 10.1002/jsfa.2740191107
|View full text |Cite
|
Sign up to set email alerts
|

Mineral composition of apples IX.—Uptake of calcium by the fruit

Abstract: The amount of calcium in mature apples appears to be related to certain storage disorders. For Cox's Orange Pippin a difference of 2 mg in a total calcium content per fruit of about 5 mg can make the difference between good and bad keeping. Most of the calcium moves into the fruit during the first few weeks of its development (approximating to the period during which the cell walls are being formed). Thereafter (during the period of cell expansion) the movement of calcium is no longer in one direction only, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

1969
1969
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 5 publications
4
27
1
Order By: Relevance
“…Similarly, Himelrick and Walker (7), and Rogers and Batjer (12) observed that Ca uptake in "Delicious' fruit increased linearly for 6 to 14 weeks following bloom and then leveled off to between 9 and 14 mg Ca per fruit at harvest. This pattern was reported for other cultivars (8,11,12,15,17). Variations in the transition period between stage I and stage II appeared to be more related to fruit weight than Ca content, since fruit Ca concentrations were similar at any given time (data not shown) while fruit weight differed markedly between years ( Figure 1A and Figure 2A).…”
Section: Resultssupporting
confidence: 59%
“…Similarly, Himelrick and Walker (7), and Rogers and Batjer (12) observed that Ca uptake in "Delicious' fruit increased linearly for 6 to 14 weeks following bloom and then leveled off to between 9 and 14 mg Ca per fruit at harvest. This pattern was reported for other cultivars (8,11,12,15,17). Variations in the transition period between stage I and stage II appeared to be more related to fruit weight than Ca content, since fruit Ca concentrations were similar at any given time (data not shown) while fruit weight differed markedly between years ( Figure 1A and Figure 2A).…”
Section: Resultssupporting
confidence: 59%
“…It has been suggested that small fruits have a higher surface area-to-volume ratio due to decreasing leaf-to-fruit ratio than large fruits from the high leaf-to-fruit ratio treatments, which can result in an increase in water loss per unit of fruit mass via transpiration, and in calcium accumulation through the xylem (Wilkinson, 1968). In treatments with low leaf-tofruit ratios, it is possible that larger amounts of water may cultivars (Chacko et al, 1982;Reddy and Singh, 1991).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…This range of fresh weight values was divided into five equal intervals, and fruit at about mid-range of each interval were taken for further analysis. Stages [6][7][8][9] were based on the range of anthocyanin values of the freeze dried fruit of greater fresh weight than those used to establish Stages 1-5. This range of anthocyanin values was divided into four intervals, and fruit with values at about mid-range of each interval selected.…”
Section: Categorization Of Fruitmentioning
confidence: 99%